2022
DOI: 10.1186/s12884-022-04958-8
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram prediction for the prediction of clinical pregnancy in Freeze-thawed Embryo Transfer

Abstract: Background This study aimed to identify multiple endometrial receptivity related factors by applying non-invasive, repeatable multimodal ultrasound methods. Combined with basic clinical data, we further established a practical prediction model for early clinical outcomes in Freeze-thawed Embryo Transfer (FET). Methods Retrospective analysis of clinical data of infertility patients undergoing FET cycle in our Center from January 2017 to September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Baseline characteristics and quality assessment of the included studies. In total, 14 cohort studies were included in the present meta-analysis (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The combined patient sample size was 4,842.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics and quality assessment of the included studies. In total, 14 cohort studies were included in the present meta-analysis (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The combined patient sample size was 4,842.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In total, 14 cohort studies were included in the present meta-analysis ( 16-29 ). The combined patient sample size was 4,842.…”
Section: Resultsmentioning
confidence: 99%
“…Screening of high quality embryos is an important element for successful pregnancy. In addition to embryo quality, the success rate of IVF is also influenced by clinical characteristics and miRNAs expression secreted by blastocysts in the culture medium 2 4 , 13 . It is assumed that the combination of clinical characteristics and miRNAs expression could be used to predict pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that these three clinical parameters are identified as significant predictors (at 5% significance level) of pregnancy. In freeze-thawed embryo transfer cycles, a simple nomogram was developed to predict the early clinical outcomes by using multiple clinical parameters 4 . In the training cohort and validation cohort, the area under the ROC curve (AUC) is respectively 0.698 and 0.699.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, nomogram is no longer limited to the study of oncology, but more applied to the study of diagnosis and prediction of non-tumor-related diseases. For example, nomograms were used to analyze the correlation between factors in genomics or proteomics and the development and progression of diseases ( 32 34 ); Nomograms were used to predict adverse outcomes in obstetrics or reproductive medicine ( 35 38 ); it can also be combined with radiomics to analyze the relationship between different image features or image segmentation factors and disease diagnosis ( 39 , 40 ), predict chronic disease incidence in orthopedics ( 41 43 ), or analyze and detect the incidence of chronic diseases combined with metabolomics ( 37 ). In addition, the display modes of nomogram are gradually diversified.…”
Section: Discussionmentioning
confidence: 99%